The Opposite Roles of White Light in Regulating Germination of Fresh and Aged Seed in Tobacco - Yao Wang; Min Zhang; Shuai Dong; Yi-Ling Liu; Zhen-Hua Li (Plants, 2021)
Light is one of the important environmental factors for seeds to evaluate whether the natural environment is appropriate for germination and subsequent seedlings emergence. The mechanism of light-mediated germination is mainly concerned with fresh seeds (FS) of model plants but is poorly understood in aged seeds. Here, the effects of light on germination of FS and naturally aged seeds (NAS) in tobacco and their relationship with plant hormones gibberellins (GA) and abscisic acid (ABA) were investigated. The results demonstrated that light promoted and inhibited the germination of FS and NAS, respectively. GA and ABA were involved in the germination control of NAS, as well as in FS. However, light suppressed GA signal and stimulated ABA signal in NAS, whereas it stimulated GA signal and suppressed ABA signal in FS. In addition, light stimulated the GA accumulation and reduction in ABA in FS while inhibiting the increase in GA level in NAS. Together, the present study demonstrates that light has opposite effects on the germination of FS and NAS, which are closely related to the metabolism and/or signaling of plant hormones ABA and GA.